2013
DOI: 10.1111/ejed.12031
|View full text |Cite
|
Sign up to set email alerts
|

Policy Formulation and Networks of Practice in European eLearning: the emergence of a European ELearning Area

Abstract: This article discusses the emergence of a European E‐Learning Area (EELA) as a consequence of three factors that can be observed in the e‐learning developments over the past decade. The first factor consists of the carving of a policy sector in e‐learning via formal instruments such as the eLearning Programme, the Lifelong Learning Programme and an array of other e‐learning policy stipulations embedded in larger policy instruments at European level (e.g. Framework Programme). The second factor is represented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…They are not doing a good job. So, if already there is little possibility and then we have underperforming projects, that is not a pity, but rather a waste As was the case with previous ICT initiatives, such as the eLearning Action Plan (Salajan, 2007(Salajan, , 2013, and with rhetorical discourse now familiar in policy narratives on the EU (Salajan, 2018), the DEAP uses the urgency of action to meet the challenges stemming from the rise of artificial intelligence and the prospect of big data, predictive analytics, the Internet of things, blockchain, etc., impacting human agency in socioeconomic and educational | 599 SALAJAN domains. Although the nature and sophistication of technologies have advanced, the challenges are similar to those addressed in the eLearning Action Plan or the eLearning Programme.…”
Section: The Third Wave: the Next Generation Of Ict Policy (2013 Onmentioning
confidence: 99%
“…They are not doing a good job. So, if already there is little possibility and then we have underperforming projects, that is not a pity, but rather a waste As was the case with previous ICT initiatives, such as the eLearning Action Plan (Salajan, 2007(Salajan, , 2013, and with rhetorical discourse now familiar in policy narratives on the EU (Salajan, 2018), the DEAP uses the urgency of action to meet the challenges stemming from the rise of artificial intelligence and the prospect of big data, predictive analytics, the Internet of things, blockchain, etc., impacting human agency in socioeconomic and educational | 599 SALAJAN domains. Although the nature and sophistication of technologies have advanced, the challenges are similar to those addressed in the eLearning Action Plan or the eLearning Programme.…”
Section: The Third Wave: the Next Generation Of Ict Policy (2013 Onmentioning
confidence: 99%
“…Furthermore, the EHEA appears to encompass other emerging areas which have not gained as much momentum as the EHEA itself but which are still recognised to be associated with European higher education. For instance, it has been suggested that the European e-Learning Area is being developed as a result of the eLearning Program promoted by the European Commission and governed by similar arrangements to those of the EHEA (Salajan, 2013). I would argue that this similarity arises from the superior status of the EHEA.…”
Section: The Potential Of the Bologna Process To Construct The Meaninmentioning
confidence: 99%
“…Current research on e‐learning policies in the EU consists of a combination of policy analysis and technical evaluation, exploring both supranational and national levels of policy influence. Thus, a number of studies suggested that the European Commission's policies stimulated collaboration in e‐learning approaches throughout the EU, but that their overall impact on the educational systems of the Member States was limited, largely because of the weak sustainability of projects designed via the e‐learning programmes operating under these policies (Dondi, Szücs & Wagner, ; Hodgson, ; Uzunboylu, ; Salajan, , ). Other studies have pointed to a need for closer alignment of national e‐learning policies with those formulated at EU level (Brown, Anderson & Murray, ; Goeman, ; Németh, ).…”
Section: E‐learning Policy Research Contextmentioning
confidence: 99%
“…It takes a holistic view in linking lifelong learning to the social dimension, which goes beyond supporting an inclusive and cohesive society by spelling out norms that should be achieved in supporting values such as gender equality, provisions for those with special needs and the elderly, inter‐cultural understanding, active citizenship, respect for human rights and democracy, promotion of linguistic diversity, etc. In this context, ICTs serve a dual role: They support the objectives of each sub‐sectoral programme through the development of pedagogically‐relevant e‐learning services and content that is tailored to the specific aims of the said sub‐programmes, and They form a stand‐alone mechanism, under the so‐called transversal programme, for supporting networks, mobility, linkages and multilateral cooperation among interested actors in the development of a European e‐learning area (Salajan, ). While e‐learning no longer has its dedicated programme, its importance is reaffirmed in the action items embedded in the Lifelong Learning Programme. No less important is the budgetary allocation specifically reserved for ICTs under the transversal programme, a section of the Lifelong Learning Programme that targets e‐learning projects and takes on the attributes of the discontinued e Learning Programme.…”
Section: Policy Framingmentioning
confidence: 99%
See 1 more Smart Citation